Hubungan Kualitas Tidur Dengan Tekanan Darah Penderita Hipertensi Pada Lansia Di Posyandu Lansia Desa Cipaku - Oktaviana, Oktaviana; Novitasari, Dwi; Dewi, Feti Kumala (JURNAL CITRA KEPERAWATAN, 2023)
Lack of sleep can affect the problem of high blood pressure triggered by the balance of the hormone cortisol. The purpose of the study was to seek knowledge relationship between sleep quality and blood pressure hypertension patients elderly integrated service post in Cipaku Village. Research applied correlational and cross sectional. Population is 158 people in 10 elderly integrated service post, apply quota sampling technique, sample research is 113 people. Instruments used a digital sphygmomanometer and Pitsburgh sleep quality index (PSQI) questionnaire. Method of data analysis is the Spearman rank test. According to gender characteristics, majority of women are 100 people (88.5%) and most age in the range of 60-70 years amount to 92 people (81.4%). Quality of sleep elderly majority have poor sleep quality as much 96 respondents (85.0%). Blood pressure, majority of the elderly had stage 1 hypertension, namely 59 respondents (52.2%). Spearman rank test results obtained p value = 0.000 <0.05 a fairly strong strength r = 0.443. Conclusion, there is relationship between sleep quality and blood pressure elderly at Integrated Service Post Cipaku Village. Suggestions for next research are to control various confounding factors that affect sleep quality and blood pressure.